Synthesis and Characterization of Nanofiber of Oxidized Cellulose from Nata De Coco - Ditpon Kotatha; Supitcha Rungrodnimitchai (International Journal of Chemical Engineering)
Oxidized cellulose (OC) nanofiber was successfully prepared from the dry sheet of Nata De Coco (DNDC) using the mixture system of HNO3/H3PO4–NaNO2 for the first time. The carboxyl content of the OC was investigated at different conditions (HNO3/H3PO4 ratios, reaction times, and reaction temperatures). The results revealed that the carboxyl content of the OC increased along with the reaction time, which yielded 0.6, 14.8, 17.5, 20.9, 21.0, and 21.0% after 0, 6, 12, 36, and 48 hours, respectively. The reaction yields of the OC ranged between 79% and 85% when using HNO3/H3PO4 ratio of 1 : 3, 1.4% wt of NaNO2 at 30°C at different reaction times. From the structural analysis, the OC products showed a nanofibrous structure with a diameter of about 58.3–65.4 nm. The Fourier transform infrared spectra suggested the formation of carboxyl groups in the OC after oxidation reaction. The crystallinity and crystalline index decreased with an increase of reaction time. The decrease of crystallinity from oxidation process agreed with the decrease of degree of polymerization from the hydrolysis of β-1,4-glycosidic linkages in the cellulose structure. The thermal gravimetric analysis results revealed that the OC products were less thermally stable than the raw material of DNDC. In addition, the OC products showed blood agglutinating property by dropping blood on the sample along with excellent antibacterial activity.